Fund Accounting: Theory and Practice. - Gustafson, George A.; Spiller, Earl A. (The Accounting Review, 1975)
Abstract Reviews the book "Fund Accounting: Theory and Practice," by Edward S. Lynn and Robert J. Freeman.